Pyrimidine and Pyrazole Linked Azetidin‐2‐ones: Entry to Novel Class of β‐Lactam Heterocycles. (7th March 2017) - Bhalla, Jitender; Bari, Shamsher S.; Rathee, Aditi; Kumar, Ashok; Bhalla, Aman
Abstract : A novel series of pyrimidine/pyrazole linked β‐lactams have been synthesized in excellent yields using a simple and efficient methodology involving conjunction of different heterocyclic substrates. All the new products were characterized on the basis of various spectroscopic techniques viz. FT‐IR, 1 H NMR, 13 C NMR, elemental analysis (CHN), 1 H‐ 1 H correlation spectroscopy ( 1 H‐ 1 H COSY) and mass spectrometry (EIMS) in representative cases. Furthermore, theoretical calculations have also been performed on representative compounds and the results were compared with C efuroxime axetil (a broad spectrum antibacterial agent). The phenomenon of tautomerism was also observed which was confirmed by different NMR experiments (D2 O exchange study and 1 H‐ 1 H correlation spectroscopy). Abstract :